THE POLITICAL TREND IN CHINA – NIGERIA EXTERNAL TRADE RELATIONS, 1999 – 2021 - PRINCEWILL OKWARA (International Studies Journal)
This paper examined the political trend in China – Nigeria external trade relations, 1999 - 2021. The general objective of this paper was to offer explanation regarding the dynamics shaping external trade relations between China and Nigeria. The paper adopted qualitative method of collection and data were source from archival and documentary sources which comprised of online and print scientific journal articles were included and excluded based on China-Nigeria external trade relations. The study findings revealed that there is significant evidence suggesting that politics at the international and domestic levels are interlinked and have also played a critical role in shaping the trends of trade between both Nigeria and China. In conclusion the paper revealed that politics has had an important role to play in the synthesis of the trends of trade relations between China and Nigeria. The dynamics of these interconnected political factors therefore offer a fuller explanation for the subsisting trade imbalance between both countries, growing trade notwithstanding. The paper therefore recommended that grassroots avenues of China-Nigeria interaction for trade should be created, sustained, and improved both in China and Nigeria.